Beyond secondary emotions: the infrahumanization of outgroupsusing human–related andanimal–related words - Viki, G. Tendayi; Winchester, Laura; Chisango, Tadios; Pina, Afroditi; Russell, Rebecca (Guilford Press, 2019)
This paper reports four series of studies that examined the infrahumanization effect using a different measure. Across the four studies, we examined whether people would associate their ingroup more with human- (vs. animal-) related words in comparison to outgroups. In Study 1, we used the Implicit Association Test (Greenwald et al., 1998) and found that participants were quicker during the compatible task (when ingroup names and human-related words shared the same response key and outgroup names and animal-related words shared the same response key) in comparison to the incompatible task. Studies 2a and 2b utilized a paper and pencil design and found that participants were more likely to link ingroup names with human-related words in comparison to the outgroup. In Studies 3a and 3b, we found that participants selected human-related words as being more characteristic of the ingroup in general than the outgroup. In Study 4, we used positive and negative words and found that participants were more likely to link human-related words with ingroup (vs. outgroup) names regardless of valence. Results are discussed in relation to their implications for infrahumanization theory.